A Supplementary Bibliography on Monopolistic Competition - Chamberlin, Edward H. (Quarterly Journal of Economics, 1948)
A Supplementary Bibliography on Monopolistic Competition Edward H. Chamberlin Edward H. Chamberlin Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 62, Issue 4, August 1948, Pages 629–638, https://doi.org/10.2307/1881771 Published: 01 August 1948